2012
DOI: 10.1007/s12576-012-0193-z
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between ghrelin and adiponectin levels in breast milk and infant serum and growth of infants during early postnatal life

Abstract: Ghrelin and adiponectin have been found in breast milk and are considered to take part in the regulation of growth and energy metabolism of infants. Our aims were to determine ghrelin and adiponectin levels in breast milk and serum samples of mothers and their infants, and to investigate the relationship between their levels and anthropometry of newborn infants during early postnatal life. Total and active ghrelin and adiponectin levels were studied in breast milk, and the serum samples of 25 healthy lactating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 25 publications
1
41
1
2
Order By: Relevance
“…Woo et al 24 found that high concentration of adiponectin is associated with weight loss and may be involved in the regulation of infantile growth. Cesur et al 18 showed that there is no significant relationship between breast milk adiponectin and growth parameters of the infants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Woo et al 24 found that high concentration of adiponectin is associated with weight loss and may be involved in the regulation of infantile growth. Cesur et al 18 showed that there is no significant relationship between breast milk adiponectin and growth parameters of the infants.…”
Section: Discussionmentioning
confidence: 99%
“…Although ghrelin receptors located on gastric epithelial cells in man may be involved in ghrelin passing from milk to infant blood, there has been little work investigating the association of breast milk ghrelin concentration and growth of breastfed infants during early postnatal life. 17,18 Besides having a role in short-term regulation of food intake, ghrelin may also have a role in long-term regulation of energy balance. The ghrelin content of maternal milk may have an important regulatory role on appetite in the infant and may have a direct effect on milk intake.…”
Section: Discussionmentioning
confidence: 99%
“…Further to the detection of ghrelin in breast milk and its receptors in human gastric epithelial cells [27], Cesur et al [28] recently speculated that from birth ghrelin in breast milk might be synthesized by mammary epithelial cells, or that it might be passed from a mother’s serum to her breast milk according to her infant’s needs.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, ghrelin and obestatin are present in breast milk and could be related to growth, appetite and food intake regulation during early life [28]. The sources of these peptides in breast milk are probably both maternal serum and breast tissue itself.…”
Section: Discussionmentioning
confidence: 99%
“…The ghrelin level increases gradually in colostrum, and in transitional and mature milk [30]. Cesur et al [31] reported that active ghrelin level in breast milk at the 4 th month of lactation significantly and positively correlated with weight gain of the infants. In new borns' levels of ghrelin were higher in SGA babies than in AGA babies.…”
Section: Ghrelinmentioning
confidence: 99%